دور المرأة العربية في النشاط الاقتصادي في عصر صدر الإسلام والعصر الراشد - جاسم، مؤيد حميدي (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2021)
إن إسهام المرأة العربية في الاقتصاد العربي وهو أمر لابد منه باعتبار أن الأرض العربية كانت البقعة التي نشأ فيها الإسلام وترعرع وكان أبناؤها رجالا ونساء هم حملة راية الإسلام للعالم كافة خصوصا وأنه رغم نقد الإسلام لبعض المواقف السلبية التي كان البعض منها موجودا فيما يتعلق بوضع المرأة في المجتمع العربي قبيل الإسلام أمثال حرمان البعض لحق المرأة في الميراث أو المهر لكنها حالات قد تكون فردية وشاذة قياسا بكثير من المواقف الجيدة الأخرى تجاه المرأة والتي أعانتنا في تحديد مدى إسهامها في اقتصاد عرب قبيل الإسلام وذلك لفهم الظروف الموضوعية التي حددت أنماط الاقتصاد العربي وهو ما أثر بصورة مباشرة وغير مباشرة على وضع المرأة العربية ومدى إسهامها في رفد جوانب ذلك الاقتصاد. ومدى حضورها التجاري المتميز وخصوصا عن طريق رفدها للقوافل التجارية أو مساهمتها في رفد الفعاليات التجارية في الأسواق العربية المتعددة برزت الكثير من الشخصيات النسائية التجارية اللواتي تبوأن مكانة بارزة في هذا النمط الاقتصادي المهم. The Arab economy, which is a must, given that the Arab land was the spot in which Islam arose and flourished, and its sons, men and women, were the bearers of the banner of Islam for the whole world, especially since despite Islam’s criticism of some negative attitudes, some of which existed regarding the status of women in Arab society prior to Islam. Proverbs of denying women the right to inheritance or dowry, but cases may be They are individual and eccentric in comparison to many other good attitudes towards women that helped us determine the extent of their contribution to the economy of Arabs prior to Islam. This is to understand the objective conditions that determined the patterns of the Arab economy, which directly and indirectly affected the status of Arab women and the extent of their contribution to supplement aspects of that economy. And the extent of its distinguished commercial presence, especially through its supply of commercial convoys or its contribution to supplying commercial activities in the various Arab markets, many female commercial figures have emerged who have assumed a prominent position in this important economic pattern.
Keywords: الأسواق العربية -- الأنماط الاقتصادية -- القوافل التجارية